Social Media Effect on Sustainable Products Purchase - Semah Ibrahim Ben Abdelaziz; Muhammad Amas Saeed; Ahmed Ziad Benleulmi (Sustainability in Logistics and Supply Chain Management: New Designs and Strategies. Proceedings of the Hamburg International Conference of Logistics (HICL), Vol. 21, 2015)
Nowadays social media have become a key platform where consumers interact with each other. Further, people are growing to be more aware of sustainability-related issues in general and sustainable products/brands-related matters in particular. This study investigates the effects of social media on consumer purchase behavior, with an exclusive focus on sustainability. In order to understand the needs and motivations of consumer engagement with sustainable products and/or brands, we surveyed a number of social media users residing in Germany. The collected data were analyzed using partial least squares structural equation modeling (PLS-SEM). Our findings helped shed the light on the effects social media have on consumers' choices regarding sustainable products/brands purchasing; they also helped identify the main drivers behind these effects.
10419/209190; https://econpapers.repec.org/RePEc:zbw:hiclpr:21
Keywords: 650; Sustainability; Social Media Dependency; Consumer Behavior; PLS-SEM